Rhodococcus equi pneumonia in foals: An assessment of the early diagnostic value of serum amyloid A and plasma fibrinogen concentrations in equine clinical practice. Issue 2 (February 2015) - Passamonti, F.; Vardi, D.M.; Stefanetti, V.; Marenzoni, M.L.; Prato, S.; Cévese, P.; Coletti, M.; Pepe, M.; Casagrande Proietti, P.; Olea-Popelka, F.
Highlights We propose an early diagnostic method for Rhodococcus equi infection in foals. Serum Amiolid A and Fibrinogen were measured weekly in foals monitored by thoracic ultrasonography for in R. equi infection. We suggest the possibility of screening using plasma fibrinogen concentrations for R. equi infection.